DNA barcoding Satyrine butterflies (Lepidoptera: Nymphalidae) in China. (3rd July 2016) - Yang, Mingsheng; Zhai, Qing; Yang, Zhaofu; Zhang, Yalin
Abstract: We investigated the effectiveness of the standard 648 bp mitochondrial COI barcode region in discriminating among Satyrine species from China. A total of 214 COI sequences were obtained from 90 species, including 34 species that have never been barcoded. Analyses of genetic divergence show that the mean interspecific genetic divergence is about 16-fold higher than within species, and little overlap occurs between them. Neighbour-joining (NJ) analyses showed that 48 of the 50 species with two or more individuals, including two cases with deep intraspecific divergence (>3%), are monophyletic. Furthermore, when our sequences are combined with the conspecific sequences sampled from distantly geographic regions, the "barcoding gap" still exists, and all related species are recovered to be monophyletic in NJ analysis. Our study demonstrates that COI barcoding is effective in discriminating among the satyrine species of China, and provides a reference library for their future molecular identification.